Report on the Development and Expansion of MRV in Thailand - International Rice Research Institute (International Rice Research Institute, 2025)
Thailand has established a highly institutionalized and sophisticated national MRV system that integrates greenhouse gas inventory tracking and emission reduction reporting into a single, streamlined workflow. Managed by the Department of Climate Change and Environment (DCCE), the system utilizes a centralized digital platform (TGEIS) to calculate emissions based on data provided by various line ministries and the Ministry of Agriculture and Cooperatives. A rigorous, multi-layered oversight structure involving technical working groups and the National Committee on Climate Change Policy ensures high data quality and alignment with international UNFCCC standards. This robust architecture not only supports domestic initiatives like the Thai Voluntary Emission Reduction scheme but also serves as a global model for transparently scaling up agricultural mitigation.